(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
In this article performing exercises to develop strength, popularizing physical education and sports, it was discussed about the strength of the wrestler without increasing his weight, the ability of the body to withstand fatigue and restore the work ability after the increase, the high level of development of physical training and the wealth of technical methods.